Emulsion electrospinning of pva nanofibers containing hypericum perforatum oil - PALA, NURSEMA (My University, 2022)
The aim of this study is to produce essential oil loaded nanofiber wound dressings from PVA, which is a biodegradable and biocompatible polymer, by emulsion electrospinning method. Hypericum Perforatum oil, known for its antibacterial, antioxidant and anti-inflammatory properties on skin disorders, was used and Kolliphor RH40 surfactant was added to emulsify oil in polymer solution. In order to examine the effect of surfactant amount on nanofiber morphology, surfactant was used at 2%, 4% and 6% (w/w) ratios. The effect of surfactant concentration on solution viscosity and fibre morphology were investigated by viscosity measurements and SEM analysis. To confirm the presence of Hypericum Perforatum oil in nanofibers structure FT-IR spectroscopy analysis were carried out. According to the results, the solution viscosity increased as the amount of surfactant increased. Additionally, it was observed that the average diameters of nanofibers, containing 2%, 4%, and 6% surfactant (w/w), increased compared to the pristine PVA nanofiber. In conclusion, the fiber morphology of Hypericum Perforatum oil-containing PVA nanofibers has been changed with the effect of surfactant.

Bu çalışmanın amacı, biyobozunur ve biyouyumlu bir polimer olan PVA'dan emülsiyon elektro-eğirme yöntemi ile uçucu yağ yüklü nanolifli yara örtüleri üretmektir. Cilt rahatsızlıklarında antibakteriyel, antioksidan ve antienflamatuar özellikleri ile bilinen sarı kantaron (hypericum perforatum) yağı katkı maddesi olarak kullanılmış ve yağın polimer çözeltisi içinde emülsiyon haline getirilmesi için Kolliphor RH40 yüzey aktif maddesi eklenmiştir. Miktarının nanolif morfolojisi üzerindeki etkisini incelemek amacıyla yüzey aktif madde %2, %4 ve %6 (w/w) oranlarında kullanılmıştır. Yüzey aktif madde konsantrasyonunun çözelti viskozitesi ve lif morfolojisi üzerindeki etkisi viskozite ölçümleri ve SEM analizi ile araştırılmıştır. Nanolif yapısında sarı kantaron yağının varlığını doğrulamak için FT-IR spektroskopi analizi yapılmıştır. Sonuçlara göre, yüzey aktif madde miktarı arttıkça çözelti viskozitesinin arttığı gözlenmiştir. Buna ek olarak, çözelti viskozitesinin artması nanoliflerin ortalama çaplarının da artmasına neden olmuştur. Sonuç olarak, sarı kantaron yağı katkılı PVA nanoliflerinin lif morfolojisinin yüzey aktif maddenin etkisiyle değiştiği gözlenmiştir.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG); emülsiyon elektro eğirme; uçucu yağ; yara örtüsü; nanolif; emulsion electrospinning; essential oil; wound dressing; nanofiber